Effectiveness Of Non-Nutritive Sucking and Murottal In Reducing Neonates' Pain Response To Needle-Related Medical Procedures - Salsabila, Andi Hafidzah Qurani; Dwimartyono, Fendy; Lantara, Andi Millaty Halifah Dirgahayu; Harahap, Muhammad Wirawan; Darussalam, Andi Husni Esa (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2025)
Neonates are newborns up to 28 days old who are highly vulnerable to infections and organ system disorders, often requiring medical intervention. One of the most common medical procedures performed on neonates is needle-related invasive procedures, such as intravenous catheter insertion and blood sampling, which can cause pain. Neonatal pain management generally avoids the use of pharmacological analgesics due to their various side effects. Therefore, effective non-pharmacological methods, such as Non-Nutritive Sucking (NNS) and Murottal therapy, are needed. This study aims to determine the effects of NNS, Murottal therapy, and their combination on reducing neonatal pain responses during needle-related medical procedures, using a quasi-experimental post-test only control group design. This study was conducted at Lamaddukelleng District General Hospital, Wajo Regency, South Sulawesi, specifically in the perinatology ward from August to October 2024 with a sample size of 92 people. The results indicate that the combination of NNS and Murottal therapy is the most effective in reducing neonatal pain responses during needle-related medical procedures, with an average pain response of 3.78 and a significance value of P > 0.001, compared to neonates who received a single intervention (either NNS or Murottal) or those in the control group.